Numerical Alloy Development for Additive Manufacturing towards Reduced Cracking Susceptibility - Wahlmann, Benjamin; Leidel, Dominik; Markl, Matthias; Körner, Carolin (Crystals, 2021)
In this work, we investigated the viability of established hot cracking models for numerically based development of crack-resistant nickel-base superalloys with a high γ′ volume fraction for additive manufacturing. Four cracking models were implemented, and one alloy designed for reduced cracking susceptibility was deduced based on each cracking criterion. The criteria were modeled using CALPHAD-based Scheil calculations. The alloys were designed using a previously developed multi-criteria optimization tool. The commercial superalloy Mar-M247 was chosen as the reference material. The alloys were fabricated by arc melting, then remelted with laser and electron beam, and the cracking was assessed. After electron beam melting, solidification cracks were more prevalent than cold cracks, and vice versa. The alloys exhibited vastly different crack densities ranging from 0 to nearly 12 mm−1. DSC measurements showed good qualitative agreement with the calculated transition temperatures. It was found that the cracking mechanisms differed strongly depending on the process temperature. A correlation analysis of the measured crack densities and the modeled cracking susceptibilities showed no clear positive correlation for any crack model, indicating that none of these models alone is sufficient to describe the cracking behavior of the alloys. One experimental alloy showed an improved cracking resistance during electron beam melting, suggesting that further development of the optimization-based alloy design approach could lead to the discovery of new crack-resistant superallo
Keywords: nickel-base alloys; CALPHAD; alloy development; hot cracking